Analisis Kesempatan Investasi dan Kebijakan Hutang terhadap Kebijakan Deviden: Studi Perusahaan LQ45 - Kurniawati, Lintang; Wijayanti, Rita; Kholis, Nur (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2021)
This study aims to determine the significance of the effect of investment opportunities, debt policy, free cash flow, profitability, and liquidity on dividend policy in LQ45 companies listed on the Indonesia Stock Exchange. The total population is 45 LQ45 companies for the period 2014 – 2018. The number of samples used is 12 companies, using purposive sampling method. There are two variables used, namely dependent and independent. The categories of independent variables are Investment Opportunities, Debt Policy, Free Cash Flow, Profitability, and Liquidity. While the dependent variable category is Dividend Policy. The analysis technique used in this research is multiple linear regression. The data is processed using SPSS 21. The results of the analysis show that the variables of Investment Opportunity, Free Cash Flow, Profitability and liquidity have an effect on Dividend Policy. Meanwhile, the Debt Policy has no effect on the Dividend Policy